Alat Potong Mekanis Mengatasi Keluhan Sakit Perajin Kerupuk Jangek - Anizar, Anizar; Yahya, Idhar; Siregar, Khawarita; Syahputri, Khalida; Tarigan, Indah Rizkya; Erwin, Erwin (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
This community service activity brought about a change in the process of cutting “kerupuk jangek” by providing a mechanical cutting tool powered by a dynamo, along with an adjustable cutting size capacity of 200 kg/hour. Previously, the production process of “kerupuk jangek” was done manually, but the cutting process was time-consuming. Craftsmen used to cut the skin while sitting on a 45 cm high wooden bench. Their right hand continuously operated the knife with the right shoulder raised, while the left hand held the sheet of skin and the neck was bent. Every day, the craftsmen manually cut 240 sheets of shin with a knife for 3 hours of work. The manual process often resulted in tired fingers and accidents where their fingers came into contact with the knife blade due to fatigue and the absence of a barrier between their finger and the knife blade. The delayed cutting process also affected the drying process, preventing the “kerupuk” from expanding properly during frying and causing a defect rate of more than 5%. The method used in this activity is providing information, training and assistance in using ergonomic work facilities. The use of the mechanical cutting tool resulted in a shorter buffalo skin-cutting process, and craftsmen were fed from bodily discomfort and potential injuries caused by contact with the knife blade.